Optical Control of Base Editing and Transcription through Light‐Activated Guide RNA. Issue 11 (8th September 2021) - Zhou, Wenyuan; Brown, Wes; Bardhan, Anirban; Tsang, Michael; Deiters, Alexander
Abstract: We developed a method to control gene activation and base editing in mammalian cells and zebrafish embryos via photochemically activated, caged guide RNAs. Four evenly distributed, caged nucleobases are installed in the 5'‐protospacer region of the gRNA to block interaction between the dCas9:gRNA complex and the dsDNA target. Upon light activation, gRNA:dsDNA hybridization is restored and catalytically dead Cas9‐based CRISPR activation or base editing is achieved. Caged gRNAs are customizable in design, offer spatiotemporal control of transcription activation and base editing in both mammalian cells and zebrafish embryos, and preserve the ability to form dCas9:gRNA complexes for enhanced gRNA stability. We hereby offer a versatile tool for conditional control of interactions between dCas9‐based regulators with their programmed genomic loci, thereby facilitating parsing of spatiotemporally complex genetic events, such as transcription regulation and single‐base mutagenesis. Abstract : Optical control of CRISPR‐Cas9 mediated base editing and transcriptional activation has been achieved using a gRNA containing photocaged nucleobases in the protospacer region. We demonstrate its effectiveness in both mammalian cells and zebrafish embryos, further expanding the set of tools available for photo‐controlled genetic manipulation in cell culture and animal models.